2022
DOI: 10.3934/jcd.2021024
|View full text |Cite
|
Sign up to set email alerts
|

A mathematical analysis of an activator-inhibitor Rho GTPase model

Abstract: <p style='text-indent:20px;'>Recent experimental observations reveal that local cellular contraction pulses emerge via a combination of fast positive and slow negative feedbacks based on a signal network composed of Rho, GEF and Myosin interactions [<xref ref-type="bibr" rid="b22">22</xref>]. As an examplary, we propose to study a plausible, hypothetical temporal model that mirrors general principles of fast positive and slow negative feedback, a hallmark for activator-inhibitor models. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…We also observed that total levels of Rac1 and RhoA in healing monolayers are reduced in Yoda1-treated compared to DMSO-treated samples (S12 Fig) . While the downregulation of Rho GTPases provides an initial insight into the mechanism underlying PIEZO1-mediated inhibition of leader cells in collective migration, a detailed characterization of this relationship surpasses the scope of work covered within this paper. In future work, we can use mathematical modeling to investigate the relationship between PIEZO1 and Rho GTPases in keratinocyte collective migration by incorporating activator-inhibitor systems for Rho GTPase feedback networks [71] and spatial dynamics [72] into our modeling framework.…”
Section: Discussionmentioning
confidence: 99%
“…We also observed that total levels of Rac1 and RhoA in healing monolayers are reduced in Yoda1-treated compared to DMSO-treated samples (S12 Fig) . While the downregulation of Rho GTPases provides an initial insight into the mechanism underlying PIEZO1-mediated inhibition of leader cells in collective migration, a detailed characterization of this relationship surpasses the scope of work covered within this paper. In future work, we can use mathematical modeling to investigate the relationship between PIEZO1 and Rho GTPases in keratinocyte collective migration by incorporating activator-inhibitor systems for Rho GTPase feedback networks [71] and spatial dynamics [72] into our modeling framework.…”
Section: Discussionmentioning
confidence: 99%
“…We also observed that total levels of Rac1 and RhoA in healing monolayers are reduced in Yoda1-treated compared to DMSOtreated samples (S12 Fig) . While the downregulation of Rho GTPases provides an initial insight into the mechanism underlying PIEZO1-mediated inhibition of leader cells in collective migration, a detailed characterization of this relationship surpasses the scope of work covered within this paper. In future work, we can use mathematical modeling to investigate the relationship between PIEZO1 and Rho GTPases in keratinocyte collective migration by incorporating activator-inhibitor systems for Rho GTPase feedback networks [71] and spatial dynamics [72] into our modeling framework.…”
Section: Plos Computational Biologymentioning
confidence: 99%
“…The direct differential method (DDM) is used for carrying out local sensitivity analysis. The DDM allows us to fully characterize each sensitivity index as a function of the independent variable [ 56 , 57 ]. Therefore, given the analytic expression of the reproduction number, we differentiate it with respect to each parameter and evaluate the resulting derivatives with the estimated (nominal) parameters for each wave.…”
Section: Sensitivity Analysismentioning
confidence: 99%